A new estimating method of minimum miscibility pressure as a key parameter in designing CO2 gas injection process - E.M. Mansour; A.M. Al-Sabagh; S.M. Desouky; F.M. Zawawy; M. Ramzi (Egyptian Journal of Petroleum)
Minimum miscibility pressure (MMP) is an important key parameter for designing any gas flooding project in enhancing oil recovery, whereas the injection must be operated at or above (MMP). This parameter will be determined before any field trial, because it is important for operator to plan suitable surface facilities and to develop injection conditions. MMP may be reliably estimated by traditional laboratory techniques, which are very costly and time consuming. Various empirical correlations for the estimation of MMP are available in literature however using them is not reliable as each correlation relates to a unique reservoir and fluid conditions. Hence none of these correlations can be used with enough confidence to estimate (MMP) and applying them is prone to errors. Therefore, the objective of this article is to search for a quick and sturdy mathematical correlation for the mathematical determination of (MMP) based on regression analysis within a shorter period of time. Finally, a comparison between the (MMP) calculated from the proposed correlation and the published ones was presented. Results ensure that the suggested new (MMP) correlation is the more accurate one. Keywords: Enhanced oil recovery, CO2 injection, Minimum miscibility pressure (MMP), Slim tube test, Sensitivity analysis